The Positive Politeness Analysis Used in Virgin-Meet the Author - Dewi Sartika; Ambalegin Ambalegin (Humanitatis : Journal of Language and Literature, 2020)
This research used qualitative research method. The theory used is Brown & Levinson (1987) about 15 positive politeness strategies. The aim of this study was to find the positive politeness strategies in Virgin-Meet the Author. Virgin is a Youtube channel. This channel contains videos that can inspire others through the good videos that are in it. One of the inspirational episodes is the Meet the Author episode where the author can tell the audience the contents of the book she/he has made so that audience can understand the contents of the book. In collecting data, this study used observational method and non-participatory techniques. Pragmatic identity method used in this research to analyze the data. The result that the researcher found were strategy of using in group identity markers, avoiding disagreement, giving and asking for reasons, includes both speaker and hearer in activity and exaggerating strategy in Virgin-Meet the Author.